HOMO CRIMINALIS: THE BIRTH OF TRANSITION PERIOD INDIVIDUAL - Міщенко, А.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The process of post-communist transformation is very complex in its various aspects. The article deals with the conception of the homo criminalis phenomenon, the transition period individual, which allows us to rethink the value of informal components of the political process in the emerging democracy.